Investigation of the effectiveness of water hyacinth as floating wetland plant on treating the nutrient pollutants - Chow M.F.; Santhiran V.; Haris H. (American Institute of Physics Inc., 2023)
A pilot study utilizing water hyacinth plants floating wetland was conducted in Universiti Tenaga Nasional, Water hyacinth was selected in this study for its abundance and suitable growth due to ideal Malaysian tropical climates. Water hyacinth were placed on floating rafts through a 4-week experimental period in water samples collected from Lake UNITEN. This study was carried out to investigate the effectiveness of water hyacinth as floating wetland plant on nutrient pollutant removal efficiencies. The efficiency of pollutant removal was evaluated in terms of as Total Suspended Solids (TSS), total phosphorus (TP) and total nitrogen (TN). The results obtained showed that removal efficiencies of up to 37.14 % for TSS, 64.44 % for TP and 98% for TN within the experimental period. The results showed that water hyacinth is very effective in removing pollutants such as TP and TN but not for TSS. 2019 Author(s).